Body Image of Emerging Women as Seen From Intensity of Instagram Use - Dwi Septyawati Reinheizher Lobo; Mariana Dinah Ch. Lerik; R Pasifikus Christa Wijaya (Journal of Health and Behavioral Science, 2022)
Women in emerging adults get a strong influence on body image from a variety of sources in the environment, including Instagram as a social media. This study aims to find out the intensity of Instagram use on body image. This type of research is quantitative with a correlational approach. Research participants were 384 female Instagram users, aged 18-24 years (mean age of 22 years). Data collection using The Instagram Intensity Scale (Cronbach'= 0.883) consists of 3 dimensions, namely the dimensions of emotional connection, the number of followers, the duration of time you use Instagram, and Body Appreciation Scale 2 (Cronbach'=0.777). Data analysis using Spearman Rank. The results of the analysis showed a significant relationship between body image and the number of followers.